Polyimide precursor, carbon nanotube resistance stabilizer and preparation method and application thereof

By developing a water-soluble carbon nanotube resistance stabilizer, using a composite system of polyimide precursor, organic tertiary amine and polyacid, the resistance stability problem of carbon nanotube film and coating at high temperature and high pressure is solved, and the resistance stability and interface bonding performance are improved.

CN119798657AActive Publication Date: 2025-04-11AVIC BEIJING AERONAUTICAL MFG TECH RES INST

Patent Information

Application Number
CN202411789167.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the resistance stability of carbon nanotube films and coatings under high temperatures and high pressures, resulting in limited application ranges.

Method used

A water-soluble carbon nanotube resistance stabilizer was developed. Through a composite system of polyimide precursor, organic tertiary amine and polyacid, a resistance stabilizer with good water solubility, high temperature and water resistance was prepared for the treatment of carbon nanotube films or coatings.

Benefits of technology

The resistance stability of the carbon nanotube film or coating under co-curing conditions of high-temperature curing resin prepregs is achieved, and the interfacial bonding performance with the composite material is good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174889210000021
    Figure BDA0005174889210000021
  • Figure BDA0005174889210000022
    Figure BDA0005174889210000022
  • Figure BDA0005174889210000031
    Figure BDA0005174889210000031
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of structure and function integrated composite materials, and particularly discloses a polyimide precursor, a carbon nanotube resistance stabilizer and a preparation method and application of the polyimide precursor and the carbon nanotube resistance stabilizer. The invention provides a carbon nanotube resistance stabilizer prepared from a polyimide precursor (namely phenolic hydroxyl group-containing polyamide acid), and the resistance stabilizer has good water solubility and is environment-friendly; meanwhile, the carbon nano tube film or coating treated by the resistance stabilizer has the characteristics of high temperature resistance and water resistance and can be matched with the co-curing condition of high-temperature curing resin prepreg, and the cured carbon nano material has good resistance stability and has an excellent interface with a composite material. The carbon nanotube resistance stabilizer provided by the invention has a good application prospect and a relatively high economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of structural and functional integrated composite materials, and specifically relates to a polyimide precursor, a carbon nanotube resistance stabilizer, and a preparation method and application thereof. Background Art

[0002] Carbon nanotubes are a type of nanomaterial with a high aspect ratio, low density and good electrical conductivity, and have received widespread attention in many fields. At present, carbon nanotubes have been used in conductive films, conductive polymers, battery electrodes and other materials. Especially in the field of conductive films, carbon nanotubes have been used to prepare various types of lightweight, highly conductive nano-modified conductive film materials. Typically, there are carbon nanotube coatings that are almost entirely composed of carbon nanotubes, buckypaper obtained by filtering carbon nanotubes, and carbon nanotube films grown by chemical vapor deposition (CVD). There are also modified conductive films composed of other materials such as carbon nanotubes and polymers, but in comparison, the former has higher conductivity due to the smaller spacing between carbon nanotubes.

[0003] However, for carbon nanotube films and coating materials that are almost entirely composed of carbon nanotubes, their conductivity will be significantly affected by the spacing between carbon nanotubes and fillers, especially when co-curing with prepreg materials of composite materials. The penetration of liquid resin and the high molding pressure during the molding process will have a huge impact on the resistance of the carbon nanotube film and coating. The resistance value is difficult to maintain and control after the material is co-cured, thus limiting its scope of application.

[0004] The prior art generally controls the spacing between carbon nanotubes by introducing a conductive binder into the carbon nanotube film, thereby making the resistance relatively stable. The conductive binder generally adopts polyvinylidene fluoride, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, etc. For example, a conductive hollow glass microsphere disclosed in Chinese patent application CN117402410A is to use a binder (selected from one or more of thermoplastic polyaryletherketone, polyvinylidene fluoride, polyetheretherketone, polyimide, polyetherimide, polyvinyl alcohol) to maintain the integrity of the conductive network of the carbon nanomaterial, and to achieve a balance between conductivity and resistance to conductive network destruction by controlling the amount of the binder. However, polyvinylidene fluoride is an oil-soluble polymer, which can cause environmental pollution, and sodium carboxymethyl cellulose, polyvinyl pyrrolidone, etc. have a lower heat deformation temperature. When co-curing with prepreg at high temperature and high pressure, carbon nanotubes are prone to displacement, resulting in uncontrolled resistance. Therefore, it is urgent to develop a water-soluble high temperature resistant carbon nanotube resistor stabilizer. Summary of the invention

[0005] The main technical problem solved by the present invention is to provide a polyimide precursor and a water-soluble carbon nanotube resistance stabilizer prepared from the precursor. The carbon nanotube film treated with the resistance stabilizer can match the co-curing conditions of the high-temperature curing resin prepreg, maintain the resistance stability of the carbon nanotube film, and have good interface bonding with the composite material.

[0006] At the same time, the present invention also provides a preparation method and application of a polyimide precursor and a carbon nanotube resistance stabilizer.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0008] A polyimide precursor, specifically a polyamic acid containing phenolic hydroxyl groups, has a structure shown in the following formula I:

[0009]

[0010] In formula I, X1 is selected from the following groups:

[0011]

[0012]

[0013] X2 is selected from the following groups:

[0014]

[0015]

[0016] X3 is selected from the following groups:

[0017]

[0018] As a preferred embodiment of the present invention, based on molar amount, y:(x+y)=0.05-0.25:1.

[0019] A method for preparing a polyimide precursor comprises the following steps:

[0020] The diamine monomer A, the (phenolic hydroxyl group-containing) diamine monomer B and the dianhydride monomer are mixed to carry out a solution polycondensation reaction to obtain a polyamic acid containing a phenolic hydroxyl group, which is a polyimide precursor;

[0021] The diamine monomer A is selected from the following compounds:

[0022]

[0023]

[0024] The diamine monomer B is selected from the following compounds:

[0025]

[0026]

[0027] The dianhydride monomer is selected from the following compounds:

[0028]

[0029]

[0030] As a preferred embodiment of the present invention, the molar ratio of the diamine monomer B to the dianhydride monomer (or the sum of the molar amounts of the diamine monomer A and the diamine monomer B) is 0.05-0.25:1. The molar ratio of the diamine monomer A to the dianhydride monomer is 0.75-0.95:1.

[0031] A carbon nanotube resistance stabilizer, the preparation raw materials of which include: polyimide precursor, organic tertiary amine and polyacid; in terms of molar weight, polyimide precursor: organic tertiary amine: polyacid=1:0.5-4:0.01-0.25.

[0032] As a preferred embodiment of the present invention, the organic tertiary amine is selected from one or more of triethylamine, pyridine, triethanolamine, dimethylisopropylamine, dimethylisopropanolamine, diethylmonoethanolamine, diethanolmonoisopropanolamine and the like.

[0033] As a preferred embodiment of the present invention, the polyacid is selected from one or more of terephthalic acid, phthalic acid, isophthalic acid, trimesic acid, maleic acid, succinic acid, naphthalene dicarboxylic acid (such as 2,6-naphthalene dicarboxylic acid), biphenyl dicarboxylic acid (such as 4,4'-biphenyl dicarboxylic acid), etc.

[0034] A method for preparing a carbon nanotube resistance stabilizer comprises the following steps:

[0035] The polyimide precursor, the organic tertiary amine and the polyacid are mixed to obtain the carbon nanotube resistance stabilizer.

[0036] An application of a carbon nanotube resistance stabilizer includes but is not limited to any of the following:

[0037] (1) Used as a treating agent for (modifying) carbon nanotube films or coatings;

[0038] (2) Used as a co-dispersing modifier for carbon nanotube slurry.

[0039] As a preferred embodiment of the present invention, when the carbon nanotube resistance stabilizer is used as a treating agent for (modifying) a carbon nanotube film or a carbon nanotube coating, the application includes:

[0040] preparing a water-based treatment solution by mixing a carbon nanotube resistance stabilizer (with water);

[0041] The (modified) carbon nanotube film or carbon nanotube coating is immersed in an aqueous treatment solution, taken out, dried, and then subjected to thermal imidization treatment to obtain a carbon nanotube material with stable resistance.

[0042] Specifically, the mass percentage concentration of the carbon nanotube resistance stabilizer in the aqueous treatment solution is 1%-16%.

[0043] Specifically, the temperature of the thermal imidization treatment is 180-260° C., and the time is 2-5 hours.

[0044] As a preferred embodiment of the present invention, when the carbon nanotube resistance stabilizer is used as a co-dispersing modifier of the carbon nanotube slurry, the application includes:

[0045] preparing a water-based treatment solution by mixing a carbon nanotube resistance stabilizer (with water);

[0046] The carbon nanotubes are made into an aqueous carbon nanotube slurry, which is then mixed with an aqueous treatment liquid to form a co-treatment slurry. The carbon nanotube coating formed by the co-treatment slurry is subjected to a thermal imidization treatment to obtain a carbon nanomaterial with stable resistance.

[0047] Specifically, the amount of the carbon nanotube resistance stabilizer in the aqueous treatment solution is 25%-280% of the mass of the carbon nanotubes.

[0048] Specifically, the temperature of the thermal imidization treatment is 180-260° C., and the time is 2-5 hours.

[0049] As a preferred embodiment of the present invention, the application further comprises: co-curing the carbon nanomaterial with stable resistance and the high temperature curing resin prepreg in a molding process to obtain a resin composite material containing the carbon nanomaterial.

[0050] Specifically, the high temperature curing resin prepreg is selected from one or more of epoxy resin prepreg, bismaleimide resin (bismaleimide resin) prepreg and the like.

[0051] Beneficial effects of the present invention:

[0052] The present invention provides a polyimide precursor and a carbon nanotube resistance stabilizer prepared from the precursor. The resistance stabilizer has good water solubility and is environmentally friendly. At the same time, the carbon nanotube film or coating treated with the resistance stabilizer has the characteristics of high temperature resistance and water resistance, and can match the co-curing conditions of high-temperature curing resin prepregs. The cured carbon nanomaterial has good resistance stability and has an excellent interface with the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 The change in the ratio of resistance to initial resistance of carbon nanotube coating treated with different concentrations of resistance stabilizer after co-curing with quartz fiber fabric reinforced epoxy resin prepreg QW120 / 1316.

[0054] Figure 2 The resistance of the carbon nanotube coating coated with resistance stabilizer / carbon nanotube slurry at different concentration ratios and the change in resistance after co-curing with quartz fiber fabric reinforced epoxy resin prepreg QW120 / 1316.

[0055] In order to more clearly illustrate the technical solution to be protected by the present invention, the drawings in the embodiments and / or experimental examples are briefly introduced above. It should be understood that the above drawings should not be regarded as any limitation on the protection scope of the present invention. DETAILED DESCRIPTION

[0056] The technical solution of the present invention is described in detail below through specific embodiments. The following embodiments are intended to further illustrate the content of the present invention in detail, but are not intended to limit the scope of protection of the claims of the present invention.

[0057] In the following examples and comparative examples, unless otherwise specified, the raw materials, reagents, equipment, etc. used are all commercially available products.

[0058] Solution Description

[0059] The present invention provides a polyimide precursor and a water-soluble carbon nanotube resistor stabilizer prepared from the precursor. The resistor stabilizer has the characteristics of being water-soluble and environmentally friendly, and has good high-temperature resistance and good water resistance after high-temperature curing. After being used to treat a carbon nanotube film or coating, it can match the co-curing process of a high-temperature epoxy resin prepreg or a bismaleimide resin prepreg, and can form a good interface bonding with a composite material matrix.

[0060] In order to achieve the purpose of the invention, the present invention creatively makes the following design and technical improvements:

[0061] (1) Water solubility, water resistance and heat resistance

[0062] In order to make the resistance stabilizer satisfy the requirements of water solubility before curing, high water resistance and good heat resistance after curing, different from the existing binder materials, the present invention innovatively designs a carbon nanotube resistance stabilizer with polyimide precursor (polyamic acid containing phenolic hydroxyl group), organic tertiary amine and polyacid as main raw materials, and the material exists in the form of polyamic acid quaternary ammonium salt before curing, and has good water solubility, so it has the characteristics of environmental friendliness. After the polyamic acid quaternary ammonium salt is cured, the final product is polyimide, so it has good water resistance and heat resistance, thereby achieving the three properties of environmental protection, high water resistance and high temperature resistance at the same time.

[0063] Preferably, in order to achieve water solubility of the material, polyamic acid forms a soluble quaternary ammonium salt with common tertiary amines such as pyridine, triethylamine, triethanolamine, diethyl monoethanolamine, diethanol monoisopropylamine, etc. When the amount of tertiary amine is higher than 20% of the carboxyl group, the system has good water solubility. In addition, the polyacids in the system also have good water solubility and can form a homogeneous water-soluble system with the polyamic acid quaternary ammonium salt.

[0064] (2) Stability issues of resistance control

[0065] In order to achieve good resistance stability control ability, it is necessary to achieve that a trace amount of polyamic acid has good heat resistance and high mechanical strength after bonding carbon nanotubes and thermal imidization, so as to cope with the higher curing temperature and curing pressure in the system during autoclave curing. However, the direct use of polyamic acid quaternary ammonium salt cannot achieve the desired effect. For example, after the comparative example 1 directly uses 3wt% of conventional polyamic acid quaternary ammonium salt (this concentration does not include the mass of tertiary amine) for treatment, for carbon nanotube coatings with a resistance of 50Ω / sq and 330Ω / sq, after co-curing with quartz fiber reinforced bismaleimide resin prepreg QW280 / 5429, the resistance after curing increases by 200%-220%, indicating that its resistance stability control ability is insufficient.

[0066] Compared with conventional polyamic acid quaternary ammonium salt, the system of the present invention adopting polyacid and polyamic acid quaternary ammonium salt containing phenolic hydroxyl group compounding has achieved good resistance control effect, and the resistance change rate is between 95%-140% (referring to embodiment 1-11). The reason is that the compounding system mainly has the following three aspects of synergistic effect: (a) conventional polyamic acid quaternary ammonium salt is easily degraded when the aqueous phase system is heated, resulting in relatively low molecular weight, while polyacid plays a cross-linking agent effect (as shown in the following formula II), improving its molecular weight and mechanical properties; (b) after conventional polyamic acid quaternary ammonium salt bonding, due to the relatively fixed position between a trace amount of binder and carbon nanotubes, higher stress is generated inside the system after drying, which easily causes bonding embrittlement, especially fracture under higher molding temperature and molding pressure, while small molecule polyacid and polyamic acid are both polyacids, with good compatibility, playing a toughening effect before cross-linking, reducing the possibility of brittle fracture; (c) the esterification cross-linking of polyacid and polyamic acid containing phenolic hydroxyl group is reversible, which reduces the curing stress to a certain extent. Therefore, the design of the compound system ensures good adhesion of the resistance stabilizer to the carbon nanotubes under low dosage, high temperature and high pressure molding conditions, thereby achieving stable control of resistance.

[0067]

[0068] (3) Interface issues of co-cured composites

[0069] Another remarkable effect of the composite system of the present invention is to improve the interfacial properties of the co-cured composite material at the same time. The traditional polyimide system is difficult to be entangled with other bonding components due to its large molecular chain rigidity and the lateral extension of the chain segments, resulting in weak bonding. The composite system of the present invention contains abundant phenolic hydroxyl and carboxyl (derived from polyacids), and the esterification reaction of the two is not sufficient, so there are a large number of active groups that can react with epoxy resin and bismaleimide resin, which significantly improves the interfacial bonding performance of the system (see Examples 1-11). In order to avoid the adverse effects caused by the excessive consumption of polyacids (such as glass transition temperature decline), the consumption of the polyacid is controlled to be 20%-60% of the molar number of phenolic hydroxyl in the polyamic acid, and the doping amount is now lower than 8% of the total mass, which has almost no effect on the glass transition temperature of the system.

[0070] (4) Application

[0071] The aqueous carbon nanotube resistance stabilizer provided by the present invention is generally dissolved in water before use, and then the carbon nanotube film or coating is treated with the aqueous treatment solution. The resistance change rate of the carbon nanotube film or coating before and after curing shows a trend of rising at both ends with the change of the amount of resistance stabilizer used, such as Figure 1 As shown. Therefore, the mass percentage concentration of the carbon nanotube resistance stabilizer in the aqueous treatment liquid needs to be controlled to be 1%-16% (preferably 2%-12%), especially for the first treatment. Microscopic analysis shows that when the concentration is low, the main reason for the increase in resistance change is the displacement and network destruction of the carbon nanotubes during the co-curing process, while at high concentrations, the main reason is that the spacing of the carbon nanotubes during the treatment process becomes larger, resulting in a rapid increase in interface resistance. It can also be seen from the figure that when the concentration of the aqueous treatment liquid is controlled within a certain range, the resistance stabilizer has a good effect, and the resistance of the carbon nanotube coating after co-curing can be controlled to 85%-110% of the initial resistance, while when the resistance stabilizer is not used, the resistance can increase to about 850%, and the controllability is poor.

[0072] In addition, the resistance stabilizer can also be dissolved in the aqueous carbon nanotube slurry and used together with the carbon nanotubes, but its amount should be 10%-280% of the mass of the carbon nanotubes. Figure 2 As shown, with the increase of the dosage ratio of the resistance stabilizer to the carbon nanotubes, the resistance of the conductive film coated with the slurry first increases slowly with the increase of the dosage ratio. When it is higher than 280%, the resistance increases rapidly, indicating that the controllability of the resistance becomes worse. At the same time, the amount of slurry required to coat the same resistance film increases rapidly. Especially after co-curing, the resistance of the film with too much stabilizer increases significantly, and the resistance controllability is poor.

[0073] It can be seen from the above designs and improvements that the material of the present invention has the following significant advantages over the prior art:

[0074] (1) In the prior art, ionic polymers such as PVDF soluble in NMP and sodium carboxymethyl cellulose soluble in water are mostly used as binders. The former causes environmental pollution and increases costs, while the latter has poor water resistance and heat resistance. The material of the present invention perfectly solves the above problems.

[0075] (2) The material of the present invention has good mechanical properties after curing, which is sufficient to maintain the structure and performance stability of the treated carbon nanotube film and coating under high-temperature resin swelling and pressure environment, solving the problem that the mechanical properties of ordinary polyamic acid quaternary ammonium salts decrease significantly during the curing process and are insufficient to maintain resistance stability.

[0076] (3) As an additional effect of the material of the present invention, the treated carbon nanotube film and coating have good interface bonding properties with the composite material.

[0077] Example 1

[0078] This embodiment provides a polyimide precursor having a structure shown in the following formula I:

[0079]

[0080] In formula I, X1 is the following group:

[0081]

[0082] X2 is the following group:

[0083] X3 is the following group:

[0084] In terms of molar amount, y:(x+y)=0.1:1.

[0085] The method for preparing a polyimide precursor provided in this embodiment comprises the following steps:

[0086] Take diamine monomer A: 108g (0.9mol) of p-phenylenediamine and diamine monomer B: 12.4g (0.1mol) of 2-hydroxyp-phenylenediamine, add them to 1500g of N,N-dimethylacetamide (DMAc), stir to dissolve, and place in an ice water bath; then weigh 218g of pyromellitic dianhydride (PMDA, 1mol), slowly add it to the above diamine solution under continuous stirring, stir for 1h after all are added, and obtain a DMAc solution of polyamic acid containing phenolic hydroxyl groups.

[0087] This embodiment provides a carbon nanotube resistance stabilizer, a preparation method and an application thereof, including:

[0088] 8.3 g (0.05 mol) of phthalic acid was added to the DMAc solution containing phenolic hydroxyl polyamic acid prepared above, and the mixture was stirred evenly; 40.4 g of triethylamine was added, and the mixture was stirred for 10 min; the mixture was then added to 9700 g of deionized water to obtain an aqueous treatment solution containing 3 wt% of carbon nanotube resistance stabilizer (when calculating the mass percentage concentration, the mass of the resistance stabilizer contained does not include the mass of triethylamine);

[0089] Take a piece of buckypaper (a carbon nanotube film formed by microfiltration of a carbon nanotube aqueous dispersion) with a surface resistance R1 of 180Ω and immerse it in the above-mentioned treatment solution; then take it out, dry it, and heat it to 240°C for 3 hours to fully imidize the resistance stabilizer;

[0090] The treated buckypaper was co-laminated with quartz fiber fabric reinforced epoxy resin prepreg QW120 / 1316, and the lamination order was [0|90] 20 , the buckypaper is placed in the middle layer; then it is cured under the QW120 / 1316 molding process, the curing pressure is 0.6MPa, the curing temperature is 180℃, and after the curing is completed, it is cooled to below 60℃ to obtain a composite material board.

[0091] Experimental method: The resistance R2 of the co-cured buckypaper was tested, and the above samples were processed to test the coating pull-off strength of the composite material.

[0092] Experimental results: The carbon nanotube resistance stabilizer prepared in this example forms a homogeneous transparent solution in water. After treatment, R2 / R1 is 1.02, while the sample prepared from untreated buckypaper is 1.58, indicating that the resistance stabilizer significantly improves the resistance stability of buckypaper. The coating tensile strength of the composite material is 34.3MPa for the treated sample, 29.5MPa for the sample prepared from untreated buckypaper, and 36.9MPa for the conventional QW120 / 1316 without intercalation.

[0093] Embodiment 2-4

[0094] Compared with Example 1, Examples 2-4 changed the amount or concentration of raw materials (as shown in Table 1), and the preparation method and application were basically the same as Example 1.

[0095] Table 1 Preparation information and performance of Examples 2-4

[0096]

[0097] Example 5

[0098] This embodiment provides a polyimide precursor, and the preparation method includes the following steps:

[0099] Take 169g (0.92mol) of diamine monomer A and 20.6g (0.05mol) of diamine monomer B, add them to 2000g of N,N-dimethylacetamide (DMAc), stir to dissolve, and place in an ice water bath; then weigh 294g (1mol) of dianhydride, slowly add it to the above diamine solution under continuous stirring, and stir for 1h after all are added to obtain a DMAc solution of polyamic acid containing phenolic hydroxyl groups.

[0100] The diamine monomer A is:

[0101] The diamine monomer B is:

[0102] The dianhydride monomer is:

[0103] This embodiment provides a carbon nanotube resistance stabilizer, a preparation method and an application thereof, including:

[0104] 11.3 g (0.096 mol) of succinic acid was added to the DMAc solution containing phenolic hydroxyl polyamic acid prepared above, and stirred evenly; 19.14 g of dimethylisopropylamine was added, and stirring was continued for 10 min; then it was added to 6254 g of deionized water to obtain an aqueous treatment solution containing 6 wt% of carbon nanotube resistance stabilizer (excluding dimethylisopropylamine);

[0105] The carbon nanotubes are dispersed in water to form a homogeneous solution with a concentration of 1.6 wt%; then the carbon nanotubes are coated on the aramid cloth to obtain a carbon nanotube conductive film attached to the aramid cloth, and the surface resistance R1 is 500Ω; the carbon nanotube conductive film is immersed in the above-mentioned treatment solution; then the carbon nanotube conductive film is taken out, dried, and heated to 220°C for 3 hours to fully imidize the resistance stabilizer;

[0106] The carbon nanotube conductive film attached to the aramid cloth is co-layered with the quartz fiber fabric reinforced epoxy resin prepreg QW120 / 1316, and the layering order is [0|90] 20 , the carbon nanotube conductive film is placed in the middle layer; then it is cured under the QW120 / 1316 molding process, the curing pressure is 0.6MPa, the curing temperature is 180℃, and after the curing is completed, it is cooled to below 60℃ to obtain a composite material plate.

[0107] Experimental method: The resistance R2 of the co-cured carbon nanotube film is detected, and the above-mentioned sample is processed to test the tensile strength of the composite material.

[0108] Experimental results: After treatment, R2 / R1 is 1.27, while the resistance ratio of the untreated carbon nanotube film after co-curing by the same method is 6.94, indicating that the resistance stabilizer significantly improves the resistance stability of the carbon nanotube conductive film. The tensile strength of the composite material is 35.9MPa for the treated sample.

[0109] Example 6

[0110] This embodiment provides a polyimide precursor, and the preparation method includes the following steps:

[0111] Take 154g (0.78mol) of diamine monomer A and 61.6g (0.22mol) of diamine monomer B, add them to 2000g of N,N-dimethylacetamide (DMAc), stir to dissolve, and place in an ice water bath; then weigh 294g (1mol) of dianhydride monomer, slowly add it to the above diamine solution under continuous stirring, and stir for 1h after all are added to obtain a DMAc solution of polyamic acid containing phenolic hydroxyl groups.

[0112] The diamine monomer A is:

[0113] The diamine monomer B is:

[0114] The dianhydride monomer is:

[0115] This embodiment provides a carbon nanotube resistance stabilizer, a preparation method and an application thereof, including:

[0116] 37 g (0.176 mol) of isophthalic acid was added to the DMAc solution of the phenolic hydroxyl polyamic acid prepared above, and the mixture was stirred evenly; 45.1 g of a mixture of triethylamine and pyridine in a mass ratio of 1:1 was added, and the mixture was stirred for 10 min; the mixture was then added to 7117 g of deionized water to obtain an aqueous treatment solution containing 6 wt% of a carbon nanotube resistance stabilizer (excluding triethylamine and pyridine);

[0117] Dispersing carbon nanotubes in water to form a dispersion with a concentration of 4.0wt%; preparing the dispersion with the aqueous treatment liquid to prepare four mixed dispersions with a carbon nanotube concentration of 2wt% and stabilizer concentrations of 0.6wt%, 1.0wt%, 2.0wt% and 4.0wt% respectively; brushing the mixed dispersions onto glass cloth, controlling the resistance R1 after drying to be 180Ω / sq; then heating the coated glass cloth to 200°C in an oven for 2h to fully imidize the resistance stabilizer, and then vacuuming to remove any residual tertiary amine;

[0118] The glass cloth-carbon nanotube film treated with different mixed dispersions was co-layered with quartz fiber fabric reinforced bismaleimide resin prepreg QW280 / 5429, and the layering order was [0|90] 10 , the glass cloth-carbon nanotube film is placed in the middle layer; then it is cured under the molding process of QW280 / 5429, the curing pressure is 0.6MPa, the curing temperature is 200℃, and after the curing is completed, it is cooled to below 60℃ to obtain a composite material board.

[0119] Experimental method: The resistance R2 of the co-cured carbon nanotube film is detected, and the above-mentioned sample is processed to test the tensile strength of the composite material.

[0120] Experimental results: The co-dispersion prepared in this embodiment has good stability and can be stored for a long time. The resistance of the carbon nanotube film coated with the above four different dispersions is 237Ω / sq, 202Ω / sq, 172Ω / sq, and 179Ω / sq, respectively, and the resistance change ratio is 132%, 112%, 95.5%, and 99.4%, respectively; the pull-off strength is 29.4MPa, 31.5MPa, 37.2MPa, and 34.2MPa, respectively, while the pull-off strength of the composite material without a resistance layer is 33.7MPa.

[0121] Embodiment 7-9

[0122] Compared with Example 6, Examples 7-9 changed the amount or concentration of raw materials (as shown in Table 2), and the preparation method and application were basically the same as Example 6.

[0123] Table 2 Preparation information and properties of Examples 7-9

[0124]

[0125]

[0126] Example 10

[0127] This embodiment provides a polyimide precursor, and the preparation method includes the following steps:

[0128] Take 223g (0.9mol) of diamine monomer A and 25.8g (0.1mol) of diamine monomer B, add them to 2000g of N,N-dimethylacetamide (DMAc), stir to dissolve, and place in an ice water bath; then weigh 294g (1mol) of dianhydride monomer, slowly add it to the above diamine solution under continuous stirring, and stir for 1h after all are added to obtain a DMAc solution of polyamic acid containing phenolic hydroxyl groups.

[0129] The diamine monomer A is:

[0130] The diamine monomer B is:

[0131] The dianhydride monomer is:

[0132] This embodiment provides a carbon nanotube resistance stabilizer, a preparation method and an application thereof, including:

[0133] 13.0 g (0.06 mol) of 2,6-naphthalene dicarboxylic acid was added to the DMAc solution containing phenolic hydroxyl polyamic acid prepared above, and the mixture was stirred evenly; 101 g of triethylamine was added, and the mixture was stirred for 10 min; the mixture was then added to 11900 g of deionized water to obtain an aqueous treatment solution containing 4 wt% of carbon nanotube resistance stabilizer (excluding triethylamine);

[0134] Take a piece of buckypaper with a surface resistance R1 of 75Ω and immerse it in the above treatment solution; then take it out, heat it to 200°C and keep it for 3 hours to fully imidize the resistance stabilizer, and then vacuum remove any residual tertiary amine;

[0135] The treated buckypaper is co-laminated with quartz fiber fabric reinforced bismaleimide resin prepreg QW280 / 5429, and the plying order is [0|90] 20 The buckypaper is placed in the middle layer and then cured under the molding process of QW280 / 5429. The curing pressure is 0.6MPa and the curing temperature is 200℃. After the curing is completed, it is cooled to below 60℃ to obtain a composite material board.

[0136] Experimental method: The resistance R2 of the co-cured buckypaper was tested, and the above samples were processed to test the tensile strength of the composite material.

[0137] Experimental results: In the above-obtained co-cured material, the surface resistance of the cured buckypaper was 78Ω, and R2 / R1 was 1.04, indicating that the resistance stabilizer significantly improved the resistance curing stability of the buckypaper. The tensile strength of the composite material was 37.8MPa.

[0138] Embodiment 11

[0139] This embodiment provides a polyimide precursor, and the preparation method includes the following steps:

[0140] Take 180g (0.9mol) of diamine monomer A and 25.8g (0.1mol) of diamine monomer B, add them to 2000g of N,N-dimethylacetamide (DMAc), stir to dissolve, and place in an ice water bath; then weigh 294g (1mol) of dianhydride monomer, slowly add it to the above diamine solution under continuous stirring, and stir for 1h after all are added to obtain a DMAc solution of polyamic acid containing phenolic hydroxyl groups.

[0141] The diamine monomer A is:

[0142] The diamine monomer B is:

[0143] The dianhydride monomer is:

[0144] This embodiment provides a carbon nanotube resistance stabilizer, a preparation method and an application thereof, including:

[0145] 24.2 g (0.1 mol) of 4,4'-biphenyldicarboxylic acid was added to the DMAc solution containing phenolic hydroxyl polyamic acid prepared above, and the mixture was stirred evenly; 45.1 g of a mixture of triethylamine and diethanol monoisopropanolamine in a mass ratio of 2:1 was added, and the mixture was stirred for 10 min; the mixture was then added to 7266 g of deionized water to obtain an aqueous treatment solution containing 6 wt% of carbon nanotube resistance stabilizer (excluding triethylamine and diethanol monoisopropanolamine);

[0146] Dispersing carbon nanotubes in water to form a dispersion with a concentration of 4.0wt%; preparing the dispersion with the aqueous treatment liquid to prepare three mixed dispersions with a carbon nanotube concentration of 2wt% and stabilizer concentrations of 1.0wt%, 2.0wt% and 3.0wt% respectively; brushing the mixed dispersions onto glass cloth, controlling the resistance R1 after drying to be 180Ω / sq; then heating the coated glass cloth to 200°C in an oven for 3h to fully imidize the resistance stabilizer, and then vacuuming to remove any residual tertiary amine;

[0147] The glass cloth-carbon nanotube film treated with different mixed dispersions was co-layered with quartz fiber fabric reinforced epoxy resin prepreg QW120 / 1316, and the layering order was [0|90] 20 , the glass cloth-carbon nanotube film is placed in the middle layer; then it is cured under the QW120 / 1316 molding process, the curing pressure is 0.6MPa, the curing temperature is 180℃, and after the curing is completed, it is cooled to below 60℃ to obtain a composite material board.

[0148] Experimental method: The resistance R2 of the co-cured carbon nanotube film is detected, and the above-mentioned sample is processed to test the tensile strength of the composite material.

[0149] Experimental results: The R2 / R1 of the three treatment solutions of the composite materials obtained above were 1.02, 0.94 and 1.01 respectively, while the resistance change rate of the carbon nanotube film without adding resistance stabilizer after coating was as high as 9.32, indicating that the resistance stabilizer significantly improved the curing resistance stability of the carbon nanotube film. The tensile strength of the composite materials was 31.5MPa, 34.6MPa and 37.2MPa respectively, showing an increasing trend, and the composite material without adding resistance stabilizer was 27.5MPa.

[0150] Comparative Example 1

[0151] This comparative example provides a polyimide precursor (i.e., conventional polyamic acid quaternary ammonium salt), and the preparation method comprises the following steps:

[0152] Take 184g (1.0mol) of diamine monomer, add it to 2000g N,N-dimethylacetamide (DMAc), stir to dissolve, and place in an ice water bath; then weigh 294g (1mol) of dianhydride monomer, slowly add it to the above diamine solution under continuous stirring, and stir for 1h after all are added to obtain a DMAc solution of polyamic acid.

[0153] The diamine monomer is:

[0154] The dianhydride monomer is:

[0155] This comparative example provides a carbon nanotube binder, a preparation method and an application thereof, including:

[0156] 60 g of triethylamine was added to the DMAc solution of polyamic acid prepared above, and stirring was continued for 10 min; then it was added to 16333 g of deionized water to obtain a treatment solution containing 3 wt % of a binder (excluding triethylamine);

[0157] Disperse carbon nanotubes in water to form a dispersion with a concentration of 2.0 wt%; apply the mixed dispersion to glass cloth by brushing, and control the resistance R1 to be 50 Ω / sq and 300 Ω / sq; then heat the coated glass cloth to 200°C in an oven for 3 hours to fully imidize the resistance stabilizer, and then remove the possible residual tertiary amine by vacuum extraction;

[0158] The glass cloth-carbon nanotube films with different surface resistances were co-layered with quartz fiber fabric reinforced bismaleimide resin prepreg QW280 / 5429, and the layering order was [0|90] 10 , glass cloth-carbon nanotube film is placed in the middle layer; then it is cured under the molding process of QW280 / 5429, the curing pressure is 0.6MPa, the curing temperature is 200℃, and after the curing is completed, it is cooled to below 60℃ to obtain a composite material board;

[0159] Experimental method: The resistance R2 of the co-cured carbon nanotube film is detected, and the above-mentioned sample is processed to test the tensile strength of the composite material.

[0160] Experimental results: After direct treatment with 3wt% conventional polyamic acid quaternary ammonium salt, the co-cured coating resistance was 151Ω / sq and 1040Ω / sq, which were 202% and 215% higher than the coating resistance (50Ω / sq and 330Ω / sq), and the tensile strength was 21.6MPa and 28.2MPa, respectively.

[0161] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A polyimide precursor, characterized in that: The polyimide precursor has a structure as shown in the following formula I: In formula I, X1 is selected from the following groups: X2 is selected from the following groups: X3 is selected from the following groups:

2. The polyimide precursor according to claim 1, characterized in that: In terms of molar amount, y:(x+y)=0.05-0.25:

1.

3. A method for preparing a polyimide precursor as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: The diamine monomer A, the diamine monomer B and the dianhydride monomer are mixed to carry out a solution polycondensation reaction to obtain a polyamic acid containing a phenolic hydroxyl group, which is a polyimide precursor; The diamine monomer A is selected from the following compounds: The diamine monomer B is selected from the following compounds: The dianhydride monomer is selected from the following compounds:

4. The preparation method according to claim 3, characterized in that: The molar ratio of the diamine monomer B to the dianhydride monomer is 0.05-0.25:1; The molar ratio of the diamine monomer A to the dianhydride monomer is 0.75-0.95:

1.

5. A carbon nanotube resistance stabilizer, characterized in that: The preparation raw materials include: a polyimide precursor according to any one of claims 1 to 2, an organic tertiary amine and a polyacid; in terms of molar weight, the polyimide precursor: the organic tertiary amine: the polyacid is 1: 0.5-4: 0.01-0.

25.

6. The carbon nanotube resistance stabilizer according to claim 5, characterized in that: The organic tertiary amine is selected from one or more of triethylamine, pyridine, triethanolamine, dimethylisopropylamine, dimethylisopropanolamine, diethylmonoethanolamine, and diethanolmonoisopropanolamine; And / or, the polyacid is selected from one or more of terephthalic acid, phthalic acid, isophthalic acid, trimesic acid, maleic acid, succinic acid, naphthalene dicarboxylic acid and biphenyl dicarboxylic acid.

7. A method for preparing a carbon nanotube resistance stabilizer as claimed in any one of claims 5 to 6, characterized in that: The following steps are involved: The polyimide precursor, the organic tertiary amine and the polyacid are mixed to obtain the carbon nanotube resistance stabilizer.

8. A use of the carbon nanotube resistance stabilizer as claimed in any one of claims 5 to 6, characterized in that: When the carbon nanotube resistance stabilizer is used as a treating agent for (modifying) a carbon nanotube film or a carbon nanotube coating, the application includes: The carbon nanotube resistance stabilizer is made into an aqueous treatment liquid; the mass percentage concentration of the carbon nanotube resistance stabilizer in the aqueous treatment liquid is 1%-16%; The (modified) carbon nanotube film or carbon nanotube coating is immersed in an aqueous treatment solution, taken out and dried, and then subjected to thermal imidization treatment to obtain a carbon nanomaterial with stable resistance; When the carbon nanotube resistance stabilizer is used as a co-dispersion modifier of carbon nanotube slurry, the application includes: The carbon nanotube resistance stabilizer is made into an aqueous treatment liquid; the amount of the carbon nanotube resistance stabilizer in the aqueous treatment liquid is 25%-280% of the mass of the carbon nanotubes; The carbon nanotubes are made into an aqueous carbon nanotube slurry, which is then mixed with an aqueous treatment liquid to form a co-treatment slurry. The carbon nanotube coating formed by the co-treatment slurry is subjected to a thermal imidization treatment to obtain a carbon nanomaterial with stable resistance.

9. The use according to claim 8, characterized in that: The temperature of the thermal imidization treatment is 180-260° C. and the time is 2-5 hours.

10. The use according to claim 8, characterized in that: The application also includes: co-curing the carbon nanomaterial with stable resistance and the high temperature curing resin prepreg under a molding process to obtain a resin composite material containing the carbon nanomaterial; The high temperature curing resin prepreg is selected from one or both of epoxy resin prepreg and bismaleimide resin prepreg.

Citation Information

Patent Citations

  • Conductive hollow glass microsphere as well as preparation method and application thereof

    CN117402410A

  • Polyimide fiber and preparation method thereof

    CN101922061A

  • Method for preparing polyimide / carbon nanotube nanocomposite

    CN102702744A

  • Humidity-sensitive biphenyl polyimide capacitor and making method thereof

    CN105111439A

  • Precursor solution of high-transparency polyimide, preparation method thereof, method for preparing transparent polyimide film by using precursor solution of high-transparency polyimide and application

    CN105860073A

Cited By

  • High-insulation and high-flame-retardant polyimide material and preparation method thereof

    CN121406131A